Dna Sequencing in the Classroom: Complete Genome Sequence of Two Earwig (Dermaptera; Insecta) Species - Maldonado-Soto, J (BioMed Central Ltd, 2023)
Background: Despite representing the largest fraction of animal life, the number of insect species whose genome has been sequenced is barely in the hundreds. The order Dermaptera (the earwigs) suffers from a lack of genomic information despite its unique position as one of the basally derived insect groups and its importance in agroecosystems. As part of a national educational and outreach program in genomics, a plan was formulated to engage the participation of high school students in a genome sequencing project. Students from twelve schools across Chile were instructed to capture earwig specimens in their geographical area, to identify them and to provide material for genome sequencing to be carried out by themselves in their schools. Results: The school students collected specimens from two cosmopolitan earwig species: Euborellia annulipes (Fam. Anisolabididae) and Forficula auricularia (Fam. Forficulidae). Genomic DNA was extracted and, with the help of scientific teams that traveled to the schools, was sequenced using nanopore sequencers. The sequence data obtained for both species was assembled and annotated. We obtained genome sizes of 1.18 Gb (F. auricularia) and 0.94 Gb (E. annulipes) with the number of predicted protein coding genes being 31,800 and 40,000, respectively. Our analysis showed that we were able to capture a high percentage (≥ 93%) of conserved proteins indicating genomes that are useful for comparative and functional analysis. We were also able to characterize structural elements such as repetitive sequences and non-coding RNA genes. Finally, functional categories of genes that are overrepresented in each species suggest important differences in the process underlying the formation of germ cells, and modes of reproduction between them, features that are one of the distinguishing biological properties that characterize these two distant families of Dermaptera. Conclusions: This work represents an unprecedented instance where the scientific and lay community have come together to collaborate in a genome sequencing project. The versatility and accessibility of nanopore sequencers was key to the success of the initiative. We were able to obtain full genome sequences of two important and widely distributed species of insects which had not been analyzed at this level previously. The data made available by the project should illuminate future studies on the Dermaptera. © 2023, The Author(s).